The flower girl wore celery - Gordon, Meryl G. (Life cycle, 2016)
"When Emma's cousin Hannah gets married, Emma is thrilled to be the flower girl. However, nothing is quite as she expected it to be, from the ring bearer whom she expected to be a bear, to her celery-colored dress, which she expected to be covered in real celery, to the wedding's two brides"--